THE RELATIONSHIP BETWEEN TEAM WORK AND PERSONALITY TRAITS: AN APPLICATION IN SECURITY SERVICES - Haydar PEKDOĞAN (International Journal of Eurasia Social Sciences, 2018)
Individual characteristics and person-focused approaches are increasingly important in modern domestic security services. Besides, security services are generally a team work perceiving, and it can be said that the propensity for team spirit indicates the success in security services at the same time. In this research, it is aimed to examine the relationship between gendarmerie staff and team work perceiving and personality traits. Survey was conducted on n = 403 gendarmerie personnel in charge of Tunceli Gendarmerie Command between January and May 2018 in this framework. According to the findings of the research, different personality traits and team work perceiving levels did not show a statistically significant difference according to the demographic characteristics of the personnel participating in the research (p> 0.05). According to the correlation analysis results, there was no statistically significant relationship between team work perceiving and personality types (p> 0.05).